Introduction to the Special Issue: Critical Reflections and Future Directions in the Study of Race, Ethnicity, and Motivation. Issue 2 (3rd April 2018) - Zusho, Akane; Kumar, Revathy
Abstract : This article introduces the special issue titled "Critical Reflections and Future Direction in the Study of Race, Ethnicity, and Motivation." We begin by framing the importance of research that considers the changing demographic landscape of the United States. Specifically, we note the increasing racial and ethnic diversity in our schools, as well as the accompanying trend of racial segregation. We discuss the two aims of the special issue, which focus on the identification of constructs that are important to understanding the schooling experiences of racially and ethnic minority youth, as well as on culturally grounded methods that can improve the operationalization of constructs such as race, ethnicity, and culture. We conclude with an overview of the four main articles and commentary that compose the special issue.